IMPLEMENTASI TEKNIK DASAR ISTRUMENT TROMPET PADA MAHASISWA PRODI MUSIK, FSP, ISI YOGYAKARTA - Purba, Ezra Deardo; Barus, Hagripa Natanael (Grenek: Jurnal Seni Musik, 2020)
The trumpet instrument is one of the instruments that was studied in depth at the Music Study Program, Faculty of Performing Arts, Yogyakarta Indonesian Art Institute. The trumpet instrument course is divided into six classes, namely intermediate instruments I, II, III and advanced instruments I, II, III. Each of these practical lecture meetings has maximum stages and targets to be able to play the trumpet instrument correctly. Several stages begin with understanding the basic techniques correctly and must be mastered by students taking trumpet instrument classes. The formulation of the problem that will be discussed is what problems are experienced by students if they do not apply basic techniques correctly and what the results are if the implementation of the basic techniques of the trumpet instrument is carried out correctly by music study program students. The methodology used is a qualitative method with a case study approach, a case study is a research strategy in which researchers carefully investigate a program, event, activity, process or group of individuals with data collection techniques in the form of observation, literature study, interviews, documentation, then analyzed. the result. In the classroom process of trumpet practice lectures, mastering the correct basic techniques is the first key to maximizing trumpet play. From a technical point of view, it will produce a good tone color, so that when you continue to the next stages, such as long tones, scales, arpegio, etude or song material that is suitable for each class level, you can blow casually more easily and can participate in practical class materials to the fullest. So in this study describes the process of implementing the correct basic techniques in preparing the quality of a professional trumpet player with maximum sound of trumpet instruments.